2015
DOI: 10.1681/asn.2014060620
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced IL-6 Functions as a Natural Brake on Macrophages and Limits GN

Abstract: IL-6 can mediate proinflammatory effects, and IL-6 receptor (IL-6R) blockade as a treatment for inflammatory diseases has entered clinical practice. However, opposing effects of IL-6 have been observed in models of GN. Although IL-6 is proinflammatory in murine lupus nephritis, protective effects have been observed for IL-6 in the nephrotoxic nephritis (NTN) model of acute crescentic GN. In light of the potential dangers of IL-6-directed treatment, we studied the mechanisms underlying the contradictory finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 60 publications
1
64
1
2
Order By: Relevance
“…Moreover, transactivation of the EGFR by other factors, such as CXCL1 and TNF-like weak inducer of apoptosis (TWEAK) (60,61), and most likely also via iRhom2/ADAM17, could also contribute to EGFR activation in Fcgr2b -/-kidneys. In addition, other iRhom2/ADAM17 substrates, such as IL-6R, may also contribute to renal damage in this model (62)(63)(64), which requires future study.…”
Section: Rhbdf2mentioning
confidence: 98%
“…Moreover, transactivation of the EGFR by other factors, such as CXCL1 and TNF-like weak inducer of apoptosis (TWEAK) (60,61), and most likely also via iRhom2/ADAM17, could also contribute to EGFR activation in Fcgr2b -/-kidneys. In addition, other iRhom2/ADAM17 substrates, such as IL-6R, may also contribute to renal damage in this model (62)(63)(64), which requires future study.…”
Section: Rhbdf2mentioning
confidence: 98%
“…Interestingly, treatment with anti-IL-6R or anti-IL-6 exacerbated renal damage in the murine model of nephrotoxic nephritis, while treatment with soluble gp130-Fc fusion protein did not [48]. The study also demonstrated that macrophages, which mediated the pathogenesis of nephrotoxic nephritis, accumulated in the kidney, expressed high levels of IL-6R and proliferated in IL-6-deficient mice; treatment with IL-6 strongly Page 16 of 64 A c c e p t e d M a n u s c r i p t 16 inhibited macrophage proliferation [48].…”
Section: Il-6 and Immune-mediated Renal Diseasesmentioning
confidence: 99%
“…53,54 In line with this, deletion of the membrane-standing IL-6 receptor from myeloid cells required for classic signaling greatly facilitated the generation of proinflammatory M1-like macrophages and thus aggravated disease in NTN on a C57Bl/6 background. 10 Using the same anti-IL-6 antibody, we failed to detect significant differences in outcome of NTN in our BALB/c mice. Conceivably, this difference relates to the choice of mouse strains, given that the BALB/c Th2-prone background leads to relatively mild macrophage and T-cell responses compared with mice on the C57Bl/6 background.…”
Section: Discussionmentioning
confidence: 74%
“…11,34,35 However, at the same time yet other reports noted a protective role of IL-6 in rat NTN 9 or conversely worsening of NTN in C57Bl/6 mice by IL-6 antagonism. 10 While it certainly is conceivable that differences in the experimental design and model of renal disease accounted for some of these discrepancies, it has also been shown that IL-6 can have a dichotomous role in renal disease. For example, in acute kidney injury, IL-6 contributes to early leukocyte-mediated damage but subsequently mediates tubular regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation